2018
DOI: 10.21649/akemu.v24i1.2344
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula (AVF) Self-Care: A Study at a Tertiary Care Hospital in Lahore, Pakistan

Abstract: Most complications associated with the use of arteriovenous fistula (AVF) access site for hemodialysis can be prevented by adopting a daily self-care plan for AVF access site. Therefore, the aim of this study was set to assess the knowledge, attitude and practice (KAP) about self-care of AVF access site amongst end stage renal disease (ESRD) patients who are on maintenance hemodialysis. Methods: This comparative cross sectional study with quantitative approach was carried out in hemodialysis unit of Shalamar I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…There were a total of seven studies: two from Nepal conducted in the years 2019 and 2021, 29,30 three from Pakistan conducted in the years 2013 and 2018, [31][32][33] and two from India conducted in the years 2012 and 2020. 34,35 Study designs and sampling techniques were clearly defined in all the studies except for Rashid et al, 32 who did not mention the sampling technique. Besides the two studies from India, 34,35 the authors in the other studies mentioned the duration of the study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were a total of seven studies: two from Nepal conducted in the years 2019 and 2021, 29,30 three from Pakistan conducted in the years 2013 and 2018, [31][32][33] and two from India conducted in the years 2012 and 2020. 34,35 Study designs and sampling techniques were clearly defined in all the studies except for Rashid et al, 32 who did not mention the sampling technique. Besides the two studies from India, 34,35 the authors in the other studies mentioned the duration of the study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Around 94% of participants reported knowledge of checking AVF thrill regularly. 32 Abraham et al 35 reported that 49% of the subjects had poor knowledge and practice in checking AVF thrills. Some participants had a poor practice of checking the thrill even after having adequate knowledge of self-care.…”
Section: Knowledge Of the Importance Of Avf Thrill Checkmentioning
confidence: 99%
See 3 more Smart Citations